Association of Susceptibility to Eating Behavior with Hemoglobin Concentration in Females - Dr. Sai Sailesh Kumar (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background There is an increase in the prevalence of eating disorders in developing countries including India. Young females were reported to be at risk of eating disorders. Hematological complications including anemia was reported to occur commonly in patients suffering with eating disorders like anorexia. Objectives The present study was undertaken to observe the association between the hemoglobin concentration with susceptibility to eating disorders in young females. Methodology A total of 30 females, with in the age group of 18-24 were part of the study after obtaining the written informed consent. The hemoglobin levels were estimated by Sahli's Method. Eat-26 questionnaire was used to assess the susceptibility to eating disorders of the participants. Data was analyzed by using SPSS 20.0. Pearson Correlation coefficient was used to observe the association between the variables. Results The mean value of hemoglobin was 10.643±1.640 gm %. The mean score of Eat-26 was 12.813±7.484. The value of R is 0.0668, which indicates positive correlation between the variables. The value of R2, the coefficient of determination, is 0.0045. Conclusion There was positive correlation between susceptibility to eating disorders and the hemoglobin concentration in the females. We recommend further detailed studies in this area to understand the mechanism of the association between the variables to develop therapeutic methods for the management of disorders associated with eating behavior.